Analyzing the Effect of Green HRM on Employee Performance: The Mediating Role of Artificial Intelligence - Charli, Chintya Ones; Suharno, Pawirosumarto; Lusiana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the era of globalization and increasing environmental awareness, organizations are required to not only pursue productivity and profits but also ensure operational sustainability through Green Human Resource Management (GHRM) strategies. This study aims to evaluate the influence of green abilities and green motivation components on employee performance and examine the mediating role of Artificial Intelligence (AI) in strengthening this relationship. A survey was conducted on 175 Civil Servants (Pegawai Negeri Sipil/PNS) in West Sumatra, and quantitative approach was used, and a survey was conducted on 175 Civil Servants (Pegawai Negeri Sipil/PNS) in West Sumatra. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS) method. The results show that green abilities significantly influence AI utilization and employee performance, while green motivation directly improves performance but has no effect on AI utilization. The role of AI is also proven to be positive, having a direct impact on performance and serving as a mediator between green abilities and employee outcomes. Conversely, AI does not mediate the relationship between green motivation and performance in a statistically significant manner. These findings emphasize the importance of building environmental competencies through green training and integrating AI-based solutions to support sustainable performance in the public sector.